A,The Upaya Peningkatan Kompetensi, Kualitas Dan Penerapan Pemasaran Secara Digital Untuk Meningkatkan Penjualan kelompok Wanita Pengrajin Rajut di Desa Kalikajar Kecamatan Kaligondang Kabupaten Purbalingga - Diah Arum probowati; Intan Indah sofiyani; Kartikasari Kartikasari Kartikasari; Nita Fernandes; Wiwiek Adawiyah Robiatul Adawiyah; Ahmad Sudjadi; Surtini surtini (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2024)
The Covid-19 pandemic was a difficult time for MSMEs in Indonesia. One of the affected MSMEs is Hira Knitting MSMEs in Kalikajar village RT 04 RW 07, Kaligondang District, Purbalingga Regency. Reduced orders during the Covid-19 pandemic caused a decline in revenue and became a serious problem for business continuity. Efforts to overcome these problems are carried out through the development of digital marketing. The method used is participatory rural appraisal (PRA) in which this method is carried out in several stages such as outreach, counseling, training, and mentoring for Hira Knitting MSME partners. The result achieved is an increase in partner knowledge regarding sales strategies carried out through digital marketing. Partners also become more knowledgeable and able to operate digital marketing strategies for the sustainability of the business they are doing and manage interesting content as a media for product promotion on social media, especially Facebook and Instagram media. Keywords: HR Competency Improvement, Digital Marketing, Social Media, MSMEs